2011
DOI: 10.2478/s13386-011-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

IRSL and post-IR IRSL residual doses recorded in modern dust samples from the Chinese Loess Plateau

Abstract: Using a set of modern/young (0 to about 200 years old) dust samples collected from the Chinese Loess Plateau the bleachability of IRSL measured at 50°C (IR 50 ) and post-IR 50 elevated temperature IRSL (measured at 225°C and at 290°C) is investigated by measuring the apparent (residual) doses recorded by these signals. Doses recorded by quartz OSL are used as a reference. Allowing for differences in dose rates it seems that both IRSL and post-IR IRSL signals yield residual doses that are significantly larger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(104 citation statements)
references
References 44 publications
9
94
1
Order By: Relevance
“…This highlights the importance of obtaining accurate and precise constraints on the residual doses of all samples and not only those deposited recently, especially when stimulated at elevated temperatures. From these results and from those of other studies (e.g., Li and Li, 2011a;Buylaert et al, 2011;Stevens et al, 2011;Nian et al, 2012), it is clear that the residual dose associated with the non-bleachable component is highly variable from sample to sample, and that sunlight bleaching tests should be routinely conducted to estimate the likely minimum size of the residual dose at the time of sample deposition.…”
Section: Residual Dose: Variability Between Samplesmentioning
confidence: 65%
See 2 more Smart Citations
“…This highlights the importance of obtaining accurate and precise constraints on the residual doses of all samples and not only those deposited recently, especially when stimulated at elevated temperatures. From these results and from those of other studies (e.g., Li and Li, 2011a;Buylaert et al, 2011;Stevens et al, 2011;Nian et al, 2012), it is clear that the residual dose associated with the non-bleachable component is highly variable from sample to sample, and that sunlight bleaching tests should be routinely conducted to estimate the likely minimum size of the residual dose at the time of sample deposition.…”
Section: Residual Dose: Variability Between Samplesmentioning
confidence: 65%
“…In practice, researchers have estimated the residual doses from modern analogues or from artificially bleached samples, and these doses have been subtracted from the equivalent dose (D e ) measured using one of the pIRIR procedures (e.g., Buylaert et al, 2011;Li and Li, 2011a). There have been no systematic investigations yet, however, of the properties of the residual signal, nor of its effect on the accuracy of pIRIR age estimates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This age overestimation of ~2 ka is not surprising given the 293 young age of the sample since it is well-known that residual, difficult-to-bleach doses affect post-IR IRSL 294 D e determination from young samples. It corresponds to a residual dose of ~6 Gy for this signal, which 295 fits within the variability of observed residual doses for well-bleached samples (i.e., samples sufficiently 296 exposed to sunlight to reset the quartz OSL signal; see, e.g., Buylaert et al, 2011). This further indicates 297 that the quartz OSL from this sample is most likely unaffected by poor-bleaching.…”
Section: Modelling: Lsd Algorithm and Geant4 212mentioning
confidence: 59%
“…It has been suggested that the fading of the pIRIR 290 signal is negligible in nature, because in very old samples measured by some studies the natural signal was close to the saturation level (Buylaert et al, 2011;Kars et al, 2012;Thiel et al, 2011b;Thomsen et al, 2011). Stability of the pIRIR 290 signal has also been inferred from age comparisons with an independent age control (Thiel et al, 2011a;Zander and Hilgers, 2013).…”
Section: Anomalous Fading Measurementmentioning
confidence: 99%